Does Balance Improve after the Application of Tai Chi Exercise Program in Post- Menopausal Women with Osteoporosis? (Baltic Journal of Sport and Health Sciences, 2017)
Background.  Osteoporosis  is  an  emerging  medical  and  socioeconomic  threat  characterized  by  a  systemic impairment of bone mass, strength, and microarchitecture. Due to degenerative changes in morphology and structure, the amount of bone fragility and fractures increases affecting balance function. Tai Chi is a traditional Chinese mind-body exercise that has the potential to overcome the impairments associated with frailty.Methods. The study involved 13 post-menopausal women with osteoporosis. All subjects participated in Tai Chi exercise program which lasted for eight weeks. Two, one-hour group training sessions were taught per week. Balance assessment was performed three times: before Tai Chi exercise program, after four weeks and after eight weeks of the application of Tai Chi exercise program. Balance measurements were conducted using platform “Sigma Balance Pad” and BESS test.Results. Research findings of “Sigma Balance Pa” showed statistically significant changes ( p < .05) in eyes opened condition while in eyes closed condition no significant changes were observed (p ≥ .05). Results of BESS test revealed statistically significant improvement of static balance after Tai Chi exercise program (p = .033).Conclusions.  Research  results  demonstrated  balance  improvement:  body  sway  and  center  of  pressure displacement speed decreased after Tai Chi exercise program. Further future research of reliability and validity of the BESS in subjects with osteoporosis should be considered.Keywords:  static balance, Sigma Balance Pad, Tai Chi Wudang.